Penegakan Hukum Tindak Pidana Kecelakaan Yang Menyebabkan Kematian Oleh Mobil Angkutan Barang Yang Mengangkut Penumpang Berdasarkan Pasal 310 Undang-Undang Nomor 22 tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Utami, Helda Lisan; Senjaya, Oci (Jurnal Ilmiah Wahana Pendidikan, 2025)
Law as a rule is essentially a judgmental view that is used as a guide to appropriate behavior. In connection with this, the task of the law is to provide legal certainty that is aimed at order and provide legal comparability that is aimed at peace. The use of goods cars to transport passengers clearly violates statutory regulations and is a serious matter. People who cause accidents that result in death must be held accountable for their actions in the hope that the perpetrator can be deterred and be more careful. As regulated in Article 310 of Law Number 22 of 2009 concerning Road Traffic and Transportation. This research uses a normative juridical method, namely a research approach by researching and studying research objects through legal principles and legislation to sharpen the research analysis which aims to find out the basics of thought, legal background and related statutory regulations. by enforcing the criminal law for accidents resulting in death by goods cars carrying passengers based on Article 310 of Law Number 22 of 2009 concerning Road Traffic and Transportation.Regarding the use of goods cars, it has also been regulated in the Road Traffic and Transport Law, namely Article 137 paragraph 4, The use of goods transport cars that are not in accordance with their intended purpose often causes accidents resulting in death. Drivers who are negligent in driving and cause death must be held responsible for their actions by proving the elements contained in Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation. By fulfilling the elements of criminal responsibility, effective law enforcement can be achieved because criminal law enforcement is the ultimum remedium or last legal effort so that the objectives of the law are carried out.